Recall of Own Speech Following Interaction With L2 Speakers: Is There Evidence for Fuzzier Representations? - Baxter, Frances; Khattab, Ghada; Krug, Andreas; Du, Fengting (Frontiers in Communication, 2022)
The aim of this study was to test claims that speakers of a first language (L1) incur cognitive and linguistic processing costs when interacting with second language (L2) speakers. This is thought to be due to the extra cognitive effort required for mapping incoming L2 speech signals onto stored phonological, lexical and semantic representations. Recent work suggests that these processing costs may lead to poorer memory of not only the L2 speech, but of one’s own produced speech during an interaction with an L2 speaker. Little is known about whether this is also moderated by working memory (WM) capacity and/or the L2 interlocutor’s proficiency. In a partial replication study of Lev-Ari, Ho and Keysar (2018), 54 healthy L1 English participants performed a WM test and then read a story and answered inference questions about it from a confederate in one of three conditions: the confederate was either a) a fellow L1 speaker; b) a Chinese L2 speaker of English with advanced proficiency or c) a Chinese L2 speaker of English with intermediate proficiency. Following a distractor task, participants were asked to recall their own answers in a surprise response-recognition questionnaire. Participants recognised their responses more accurately after interacting with the L1 speaker compared with the advanced L2 speaker but not compared with the intermediate L2 speaker. WM capacity correlated with higher accuracy when interacting with the L1 speaker, but with lower accuracy when interacting with the intermediate L2 speaker. These results suggest that effortful processing of input may lead to fuzzier lexical and/or semantic representations of one’s own produced speech. However, the lack of significance in recall accuracy between the L1 and the intermediate L2 condition suggests other factors may be at play. Qualitative analyses of the conversations provided insights into strategies that individuals adopt to reduce cognitive load and achieve successful communication.